Magneto-optical recording materials (IEEE Press, 2000)
"As digital data storage technology undergoes enormous change, electrical engineers, physicists, and materials scientists need to keep pace with the materials requirements for recording media. Expert contributors -- together with world-class authorities Richard J. Gambino and Takao Suzuki -- bring you a practical, comprehensive guide to materials design and selection for magneto-optical storage media. This authoritative book explores multilayered thin films, exchanged coupled layers, materials used in current products, and materials of potential interest not yet available in practical applications. A detailed analysis concerning the physics of magneto-optical recording will help you make informed decisions about materials properties. You will also find an extensive discussion of systems and engineering design features for magneto-optical storage devices. This discussion will help you to understand how materials properties impact system performance.